Clouds of Witness - Sayers D. Dorotny (New English library)
A new edition of the famous crime novel, first published in 1926. A man is found shot, and the Duke of Denver is charged with the murder of his sisters fiance. His brother, Lord Peter Wimsey, is then called to investigate the crime.